Administrative reform a conceptual analysis - Quah, Jon S.T. (1976)
A review of the literature on administrative reform reveals the lack of a consensus among public administration scholars as to how the term should be defined. While varying definitions of this concept abound, most of these definitions fail to identify its goals as well as to consider the institutional and attitudinal aspects of reform. Aside from offering a tentative definition which avoids these shortcomings, this article reviews the literature on this concept with particular emphasis on the goals, approaches and obstacles to administrative reform. It identifies the major goal of administrative reform as the improvement of the level of organization effectiveness of organizations concerned. It reexamines the conditions under which the use of the comprehensive or the incremental approach to administrative reform may be more feasible, and discusses how such factors as history, technology, culture, society and economy can obstruct the implementation of these reforms.
Keywords: Administrative reform; Public administration